Understanding Physical Activity in the Daily Lives of Bangladeshi and Pakistani Elders in Great Britain. (26th March 2014) - Victor, Christina R.
Abstract : In the United Kingdom, there are physical activity guidelines specifically for older adults. Self-report data indicate that approximately 15% of those achieved 65+ the activity target of 30 minutes of moderate intensity exercise on 5 (or more) days a week and 30% when the 150 minutes may be achieved in 10-minute (or greater) bursts. Levels of activity are higher among men, the more affluent, and those aged 65–74 but we have little evidence about levels of activity among the ageing ethnic minority population. Reanalysis of 109 interviews conducted with people aged 50+ from Bangladeshi and Pakistani communities was undertaken to explore how participants talk about physical activity in terms of their daily lives. Few, 13 participants (7 females), reported that physical activity and/or exercise formed part of their daily routine; a further 7 had been advised to take exercise by their doctors but had not done so and 9 described why they could not exercise. Barriers to exercise included lack of time (because of work or childcare) and cultural factors such as ideas about age and gender appropriate behaviour. We need to develop appropriate interventions to encourage exercise which address these cultural factors and general barriers to exercise.